Optimal output-feedback temperature regulation of a catalytic reverse flow reactor PDEs model. (July 2021) - Aksikas, Ilyasse
Abstract: In this work, control and estimation problems have been studied for a catalytic reversal flow reactor (CFRR). A stabilizing compensator is developed on the basis of the infinite-dimensional state-space description of the CFRR. Linear–quadratic technique is used to design both an optimal state-feedback controller and an output injection operator. The later is developed based on the duality fact between regulation and estimation. Indeed, the output injection operator is the adjoint of the feedback control operator of the dual process. The developed compensator is tested numerically for the catalytic combustion of lean methane emissions. Highlights: Description of the reverse flow reactor by PDEs mathematical model. Linear–quadratic control technique is used to regulate the temperature in the reactor. Duality feature is used to design an observer to estimate the temperature. Simulations are performed, for the catalytic combustion of lean methane emissions. Evaluate the closed-loop performance under the developed compensator.